La Promoción y Publicidad en las Ventas de la Empresa Metal Mecánica “Metalizar” de Riobamba - Piray Vela, Aylin Marcela (2023)
ABSTRACT: The present research work entitled "Promotion and advertising in the sales of the metal mechanics Metalizar company of Riobamba, has the problem that it lacks a qualified team that carries out a marketing plan aimed at strengthening through Promotion and advertising the offering of the company's products and services, and its objective is to propose promotional and advertising strategies to increase the sales of the Metalizar de Riobamba company, in the same way diagnose the method, also analyze the influence and design advertising and promotion strategies. Metalmecánica Metalizar is a family business created in 1992 located on Av. Luis Cordovez and Captain Edmundo Chiriboga's objectives are to achieve optimal profitability to become a reliable source of employment for society, guarantee the company's development, manufacture products, and offer high-quality services. The population in this research work is infinite; based on INEC data from 2010, there is a total of 200,034 economically active people that the company Metalizar wants to reach; data collection surveys were applied to 384 people, this being the sample, and thus be able to obtain more precise data for their analysis. To conclude, the alternative hypothesis is accepted, and the null hypothesis is rejected; this means that Promotion and advertising affect Metalizar's sales. Promotion and advertising strategies have been proposed so that the company can put them into practice and thus be able to increase its sales; a budget of $15,850.00 will allow the company to increase its sales and, at the same time, become known in the city of Riobamba, it should be noted that this proposal is flexible and can be adjusted to the needs of the company.